EFFECT OF GOOD CORPORATE GOVERNANCE PRACTICES TOWARD THE MOSQUE ACCOUNTING APPLICATION SURVEY OF MOSQUE IN BOGOR - Retno Martanti Endah Lestari; Agung Fajar Ilmiyono; Jalaludin Al Mahali (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2019)
This research was designed, one of which is to provide input to the Ministry of Religion and DKM in particular that mosque financial management must be transparent and accountable by applying the mosque accounting application in its implementation so that the targeted financial management of mosque governance can be easily achieved. In reality, as many as 30 mosques were selected in Bogor, that the effect of GCG application on the application of mosques in 30 selected mosques, which involved the principles of accountability, transparency, responsibility, independence and the principle of reasonableness had no influence on the process of applying the mosque application, this is certainly a lack of knowledge the mosque DKM how important is the implementation of good corporate governance. The purpose of this study is to determine the economic characteristics of the area in mosques in the Bogor area and whether the application of good corporate governance can affect the application of mosque accounting applications. This type of research is verification with an explanatory survey. Data collection method using a questionnaire. Data collection techniques from primary data and secondary data. Sampling using a purposive sampling method as many as 30 mosques in the Bogor Region. It can be concluded that the economic characteristics of the area at the 30th Mosque selected, still not evenly distributed, this can be seen from the different educational backgrounds of the DKM Mosque and the different area of the mosque and the results of the research data test application of good corporate governance has no influence on the application Mosque Accounting Application.